احكام حق حبس الثمن للضمان - د. عبد العالي صالح العكيدي (PROSPECTIVE RESEARCHES, 2023)
The right for perventing the price happens when there are tow debts opposing and linked together when the source of this debt is a part of the commitment whether creditors and at the sometime, regardless of the source of the debt . The Iraqi legistlator regards the payment without execution a part of prevention or he may mix them, since the impersonal is not regarded as a civil right or personal because it occurs on the basis of thoides of some commitments based on then ides of equality, the Iraqi legistlator stated in a general principle the means of insurance of the rights of creditors, then he gave other text which he dealt with as an application of the general principle. The Iraqi law tackled this subject and augmented with some decisions as a lowful application in this respect, the application shows some importance for this subject.